Polyvinyl alcohol film and method for producing optical film using same

By controlling the crystal long period ratio of PVA films through small-angle X-ray scattering, the formation of swelling wrinkles is suppressed, allowing for the production of thin optical films with improved productivity and reduced breakage.

JP7601875B2Active Publication Date: 2024-12-17KURARAY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022533923
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-06-23
Publication Date
2024-12-17
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

Conventional polyvinyl alcohol (PVA) films break during the stretching process when attempting to manufacture thinner optical films due to the formation of swelling wrinkles during the swelling process.

Method used

The PVA film is engineered with a specific crystal long period ratio and controlled within a range determined by small-angle X-ray scattering measurements, suppressing the formation of swelling wrinkles and film breakage during the stretching process.

Benefits of technology

The solution enables the production of thin optical films with high productivity by preventing film breakage and maintaining film integrity during the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601875000002
    Figure 0007601875000002
  • Figure 0007601875000001
    Figure 0007601875000001
Patent Text Reader

Abstract

Provided are: a PVA film capable of, even when having a small thickness, suppressing generation of swell wrinkles in a swelling step when producing an optical film; and a method for producing an optical film using said PVA film. The polyvinyl alcohol film according to the present invention satisfies formula 0.15≤(Ds-Da) / Da<0.3, where Ds represents a crystal long period obtained from a small angle X-ray scattering measurement performed in a water / methanol solvent mixture (volume ratio: 2 / 8), and Da represents a crystal long period obtained from a small angle X-ray scattering measurement performed before the film is immersed in the solvent mixture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyvinyl alcohol film and a method for producing an optical film using the same. [Background technology]

[0002] Polarizing plates, which have the function of transmitting and blocking light, are basic components of liquid crystal displays (LCDs) along with liquid crystals, which change the polarization state of light. LCDs are now used in a wide range of applications, including small devices such as calculators and watches, laptops, LCD monitors, LCD color projectors, LCD televisions, car navigation systems, mobile phones, and measuring instruments used both indoors and outdoors. LCD televisions and LCD monitors, among other LCD application fields, are becoming larger and thinner, and as the glass used becomes thinner, polarizing plates are also required to become thinner from the perspective of shrinkage stress.

[0003] Polarizing plates are generally manufactured by subjecting a polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be abbreviated as "PVA") to a dyeing process, a stretching process (uniaxial stretching process), and, if necessary, a fixing process using a boron compound or the like to manufacture a polarizing film, and then laminating a protective film such as a triacetate cellulose (TAC) film onto the surface of the polarizing film. Therefore, in order to achieve a thinner polarizing plate, it is required to manufacture a thinner polarizing film using a thinner PVA film. Specifically, the thickness of the PVA film is required to be 60 μm or less, and further 50 μm or less.

[0004] Patent Document 1 describes that by using a PVA film having a specific range of long period and amorphous thickness determined by small-angle X-ray scattering, a polarizing film having excellent in-plane uniformity of polarization performance (degree of polarization, single transmittance) and corresponding to larger area and higher definition can be obtained. Patent Document 2 describes that by using a PVA film having a specific range of crystal long period in water, a polarizing film having high absorbance in the long wavelength region and high degree of polarization can be produced. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-188655 A [Patent Document 2] WO2013 / 146147 publication Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the case of a conventionally known PVA film, when the thickness of the PVA film is reduced in order to make the optical film such as a polarizing film thinner, the PVA film is likely to break during the stretching process when manufacturing the optical film such as a polarizing film. That is, when the thickness of the PVA film is thin, swelling wrinkles are generated in the PVA film during the swelling process when manufacturing the optical film such as a polarizing film, and the PVA film is likely to break from the swelling wrinkles during the subsequent stretching process. Here, swelling wrinkles refer to wrinkles generated by the PVA film swelling with water in the swelling process.

[0007] Therefore, an object of the present invention is to provide a PVA film that can suppress the occurrence of swelling wrinkles in the swelling step when producing an optical film, even when the film is thin, and a method for producing an optical film using such a PVA film. [Means for solving the problem]

[0008] The inventors have conducted extensive research focusing on the change in the crystal structure, particularly the long crystal period, of a PVA film before and after swelling, and have found that by setting the ratio of the change in the long crystal period before and after immersion of a PVA film in a water / methanol mixed solvent to the long crystal period before immersion within a specific range, it is possible to prevent the PVA film from developing swelling wrinkles during the swelling process when producing a polarizing film such as an optical film, and as a result, to prevent the PVA film from breaking during the stretching process. Based on this knowledge, further research has led to the completion of the present invention.

[0009] That is, the present invention relates to the following [1] to [6]. [1] A PVA film, in which the crystalline long period Ds determined by small-angle X-ray scattering measurement performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystalline long period Da determined by small-angle X-ray scattering measurement performed before immersion in the mixed solvent satisfy the following formula: 0.15≦(Ds-Da) / Da<0.3; [2] The PVA film according to [1], wherein the crystal long period Ds is 12.0 to 16.0 nm; [3] The PVA film according to [1] or [2], having an average thickness of 15 to 60 μm; [4] The PVA film according to any one of [1] to [3], which is a raw film for producing an optical film; [5] A method for producing an optical film, comprising uniaxially stretching the PVA film according to any one of [1] to [4]; [6] A method for producing the optical film according to [5], comprising a swelling step of swelling a PVA film. Effect of the Invention

[0010] According to the PVA film of the present invention, even if the PVA film is thin, the generation of swelling wrinkles in the PVA film during the swelling step in the production of the optical film can be suppressed. Therefore, according to the PVA film of the present invention, the breakage of the PVA film during the stretching step in the production of the optical film can be suppressed, and a thin optical film can be produced with good productivity. [Brief description of the drawings]

[0011] [Figure 1] This is a reference diagram for setting the peak-top scattering vector q (nm-1) in a scattering curve obtained by small-angle X-ray scattering measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be specifically described below.

[0013] <PVAフィルム> (Small angle X-ray scattering measurement) The PVA film of the present invention has a long crystal period Ds determined by small-angle X-ray scattering measurement performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and a long crystal period Da determined by small-angle X-ray scattering measurement performed before immersion in the mixed solvent, which satisfy the formula 0.15≦(Ds-Da) / Da<0.3.

[0014] In small-angle X-ray scattering measurements, when a sample is irradiated with X-rays, the diffraction that occurs when the X-rays are scattered or interfered with by electrons around the atoms is analyzed. In particular, by analyzing the diffraction that appears in the low-angle region of 2θ<10° or less, the structure of the sample being measured can be evaluated, and it is generally said that structures of a few nm to tens of nm in size can be evaluated. For example, the crystal long period of the sample being measured (the average value of the distance between crystals randomly present in a polymer) can be evaluated.

[0015] In general, when X-rays are incident on a material with a regular arrangement, the X-rays are scattered. The scattered X-rays interfere with each other and reinforce each other in specific directions. According to the Bragg equation, diffracted X-rays due to this scattering can be observed only in directions that satisfy the Bragg equation 2d·sinθ=nλ, where d is the lattice distance, θ is the Bragg angle, and λ is the wavelength of the X-ray.

[0016] In a PVA film, there are crystalline parts (lamellar crystals) in which the molecular chains of PVA are folded, and amorphous parts in which the molecular chains of PVA are unfolded. In the present invention, the average intercrystalline distance between the crystalline parts (lamellar crystals) is taken as the crystal long period. This crystal long period can be determined from the diffraction peak of the scattering curve obtained by subjecting the PVA film to small-angle X-ray scattering measurement. When the PVA film is a raw film for producing optical films, the diffraction peak resulting from this crystal long period is calculated by dividing the scattering vector q (nm -1 ) is 0.5 nm -1 It is commonly known to appear in the vicinity.

[0017] (Calculation of crystal long period) In the present invention, the PVA film to be measured for small-angle X-ray scattering was prepared as follows and used as a measurement sample. First, the PVA film to be measured was cut into multiple pieces with a size of 2 cm x 1 cm, regardless of the width direction (TD direction) or the machine flow direction (MD direction). After storing the cut PVA film for 24 hours under conditions of a temperature of 20 ° C. and a humidity of 65%, 10 sheets were stacked in a measurement cell to obtain a measurement sample. Here, the crystal long period obtained from the scattering curve obtained when the measurement sample was subjected to small-angle X-ray scattering measurement in air (temperature 20 ° C., humidity 65%) is the crystal long period Da described below. Similarly, multiple PVA films cut into a size of 2 cm x 1 cm were immersed in a water / methanol mixed solvent (volume ratio: 2 / 8) for 24 hours, and then 10 sheets were stacked in a measurement cell filled with the mixed solvent to obtain a measurement sample. Here, the crystal long period obtained from the scattering curve obtained when the measurement sample was subjected to small-angle X-ray scattering measurement is the crystal long period Ds described below.

[0018] In preparing the measurement sample, the measurement cell used 7.5 μm thick Kapton films as the window materials on the incident light side and the reflected light side, and the distance between the window materials was about 1.5 mm. With this structure, the measurement sample can be sealed in the measurement cell. In addition, by using this measurement cell, the PVA film to be measured can be placed in the mixed solvent in the normal measurement arrangement in the measurement device described below.

[0019] In the present invention, small angle X-ray scattering measurements were performed using a nanoscale X-ray structure evaluation device "Nano Viewer" (manufactured by Rigaku Corporation). The measurement conditions were as follows.

[0020] Transmission measurement X-ray:CuKα ray Wavelength: 0.15418nm Output: 40kV-20mA First slit: φ0.4mm Second slit: φ0.2mm 3rd slit: φ0.45mm Detector: Semiconductor 2D detector PILATUS-100K (measurement area = 33.5 x 83.8 mm) Pixel size: 0.172mm square Camera length: 1004.51mm Beam stopper diameter: 4mm X-ray exposure time: 1 hour Measurement mode: Normal measurement Environmental temperature: room temperature (20℃)

[0021] In small-angle X-ray scattering measurements of PVA film, scattering from the PVA film is overlapped with scattering from the slits and other devices, the air through which the X-rays pass, and the solvent inside the cell, so it is necessary to correct for these scatterings as background. For this reason, corrections were made by subtracting the above-mentioned background scattering intensity, which was calculated separately, from the scattering intensity obtained by measuring the measurement sample. In addition, the scattering vector q (nm -1 ) is integrated in the azimuth direction to obtain the scattering vector q(nm -1 The scattering curve was obtained by deriving the relationship between the one-dimensional profile of the scattering intensity I(q) and the scattering intensity I(q).

[0022] As described above, in the small-angle X-ray scattering measurement of the PVA film, the diffraction peak due to the long crystal period of the PVA film is located in the scattering curve with the scattering vector q (nm -1 ) is 0.5 nm -1In the present invention, the scattering vector q (nm -1 The crystal long period Ds and the crystal long period Da were calculated from the value of the scattering vector q (nm -1 ) is in the range of 0.2 or more and 1.0 or less, this is the inflection point where the scattering curve becomes upwardly convex (see Figure 1).

[0023] The scattering vector q(nm -1 The formula for calculating the crystal long period Ds and the crystal long period Da from the values ​​of Crystal long period (nm) = 2π / q

[0024] In the present invention, it is important that the crystalline long period Ds determined from small-angle X-ray scattering measurement performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystalline long period Da determined from small-angle X-ray scattering measurement performed before immersion in the mixed solvent satisfy the formula 0.15≦(Ds-Da) / Da<0.3.

[0025] Here, (Ds-Da) / Da means the increase rate of the crystal long period before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). By performing small-angle X-ray scattering measurement in a water / methanol mixed solvent (volume ratio: 2 / 8), the crystal dissolution state at the initial swelling stage when the PVA film is immersed in water can be evaluated. The upper limit of (Ds-Da) / Da (hereinafter sometimes referred to as the "increase rate of the crystal long period") is preferably 0.3, more preferably 0.25. The lower limit of (Ds-Da) / Da is preferably 0.15, more preferably 0.18. If the increase rate of the crystal long period is too large, the PVA film will swell in a solvent such as water, and the distance between the lamellar crystals in the PVA film will easily increase. In other words, if the increase rate of the crystal long period is too large, it is considered that the amorphous part in the PVA film will easily take up a solvent such as water. Therefore, in the swelling process when manufacturing an optical film such as a polarizing film, the PVA film is likely to absorb water contained in the swelling treatment bath, and as a result, the PVA film is likely to spread and swelling wrinkles are likely to occur. On the other hand, if the increase rate of the crystal long period is too small, it is considered that the amorphous part in the PVA film is unlikely to absorb solvents such as water. As a result, in the stretching process when manufacturing an optical film such as a polarizing film, the stretching tension of the PVA film becomes high, and the PVA film may be prone to breakage.

[0026] In the present invention, the crystal long period Da of the PVA film, determined by small-angle X-ray scattering measurement performed before immersion in a water / methanol mixed solvent (volume ratio: 2 / 8), is preferably 10.0 nm or more. The crystal long period Da is preferably 15.0 nm or less. Here, the crystal long period Da is determined by small-angle X-ray scattering measurement before immersion in a water / methanol mixed solvent (volume ratio: 2 / 8), that is, in air (temperature 20°C, humidity 65%). The crystal long period Da is more preferably 11.0 nm or more. The crystal long period Da is more preferably 14.0 nm or less. If the crystal long period Da is less than 10.0 nm, it is estimated that the crystal structure has a small thickness of lamellar crystals in the PVA film. If the thickness of the lamellar crystals is small, when the PVA film is immersed in a swelling treatment bath in the swelling process for producing an optical film such as a polarizing film, the microcrystals of the lamellar crystals in the PVA film are likely to dissolve, and the PVA film may become soft and prone to swelling wrinkles. On the other hand, if the crystal long period Da is greater than 15.0 nm, it is estimated that the thickness of the lamellar crystals in the PVA film is large, or the distance between the lamellar crystals is long and the crystal structure has many amorphous parts. In the former case, the lamellar crystals in the PVA film are not sufficiently dissolved in the swelling process for producing an optical film such as a polarizing film, and the stretching tension of the PVA film may become too high in the stretching process. In the latter case, when the PVA film is immersed in a swelling treatment bath in the swelling process for producing an optical film such as a polarizing film, the amorphous parts in the PVA film are likely to take up the water contained in the swelling treatment bath, and the PVA film may spread and prone to swelling wrinkles.

[0027] In the present invention, the crystal long period Ds obtained from the small-angle X-ray scattering measurement performed in a water / methanol mixed solvent (volume ratio: 2 / 8) is preferably 12.0 nm or more. The crystal long period Ds is preferably 16.0 nm or less. The crystal long period Ds is more preferably 13.0 nm or more. The crystal long period Ds is more preferably 15.0 nm or less. If the crystal long period Ds exceeds 16.0 nm, when the PVA film or an optical film such as a polarizing film obtained from the PVA film absorbs moisture, the molecular chain of PVA is likely to spread, and the wet heat resistance of the PVA film or the optical film may be deteriorated. On the other hand, if the crystal long period Ds is less than 12.0 nm, when the PVA film is immersed in a swelling treatment bath in the swelling step in producing an optical film such as a polarizing film, the amorphous part in the PVA film is unlikely to take up the water contained in the swelling treatment bath, and the stretching tension of the PVA film may become too high in the stretching step.

[0028] In the present invention, methods for adjusting the crystal long period Ds and the crystal long period Da and controlling the increase rate of the crystal long period within the above range include (1) a method for adjusting the crystalline state of PVA by controlling the conditions of extrusion, drying, and heating when forming a film, (2) a method for adjusting the extent of the amorphous part in the PVA film by adjusting the degree of interaction between PVA molecular chains depending on the type of PVA (degree of saponification, amount of modification, etc.), (3) a method for adjusting the size of lamellar crystals by adding a plasticizer, etc., (4) a method for adjusting the crosslinked structure between PVA molecular chains by adding a crosslinking agent, etc., to adjust the crystalline state of PVA or the extent of the amorphous part, and a combination of these methods.

[0029] When the increase rate of the crystal long period is controlled to the above range by the above method (1), the discharge conditions for film formation are, for example, preferably such that the volatile content of the film formation solution is 10% by mass or more and 40% by mass or less, and the shear rate at the outlet of the film-form discharge device is 75 s -1 More than 1000s -1The drying conditions when forming the film are, for example, preferably a surface temperature of the support on which the film-forming solution is dripping is 110° C. or less, the temperature of the hot air blown onto the non-contact side of the PVA film on the support is 150° C. or less, and the temperature of the drying oven or the average temperature of the drying roll (average surface temperature of the drying roll) is 110° C. or less. The heating conditions when forming the film are, for example, preferably a surface temperature of the heat treatment roll is 135° C. or less.

[0030] When the increase rate of the crystal long period is controlled to the above range by the above method (2), the saponification degree of PVA is preferably, for example, 85 mol% or more and 95 mol% or less. Also, the modification amount of PVA (the proportion modified with a monomer other than polyvinyl alcohol unit) is preferably, for example, 0.3 mol% or more and 8 mol% or less.

[0031] When the increase rate of the crystal long period is controlled to the above range by the above method (3), the content of the plasticizer is preferably 2 parts by mass or more and 20 parts by mass or less per 100 parts by mass of PVA. In addition, it is preferable to use ethylene glycol, glycerin, diethylene glycol, or diglycerin as the plasticizer.

[0032] (PVA) The PVA contained in the PVA film of the present invention may be a polymer produced by saponifying a vinyl ester polymer obtained by polymerizing a vinyl ester monomer. Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. Among the above, vinyl acetate is preferred as the vinyl ester monomer.

[0033] The vinyl ester polymer is not particularly limited, but is preferably a polymer obtained by using only one or more vinyl ester monomers as a monomer, and more preferably a polymer obtained by using only one vinyl ester monomer as a monomer. The vinyl ester polymer may be a copolymer of one or more vinyl ester monomers and another monomer copolymerizable with the one or more vinyl ester monomers.

[0034] Examples of other monomers include ethylene; olefins having 3 to 30 carbon atoms, such as propylene, 1-butene, and isobutene; acrylic acid or a salt thereof; acrylic acid esters, such as methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, i-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or a salt thereof; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, methacrylic acid, and the like. Methacrylic acid esters such as i-propyl acrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamides such as acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetone acrylamide, acrylamidopropanesulfonic acid or a salt thereof, acrylamidopropyldimethylamine or a salt thereof, and N-methylolacrylamide or a derivative thereof; methacrylamide derivatives such as methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidepropanesulfonic acid or a salt thereof, methacrylamidepropyldimethylamine or a salt thereof, N-methylolmethacrylamide or a derivative thereof; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or a salt, ester, or acid anhydride thereof; itaconic acid or a salt, ester, or acid anhydride thereof; vinyl silyl compounds such as vinyltrimethoxysilane; and isopropenyl acetate.The vinyl ester polymer may have structural units derived from one or more of the other monomers mentioned above.

[0035] The proportion of structural units derived from other monomers in the vinyl ester polymer (hereinafter, sometimes referred to as the "degree of modification") is not necessarily limited as long as it does not impede the effects of the present invention, but it is preferably 15 mol % or less, more preferably 5 mol % or less, even more preferably 1 mol % or less, and in some cases even more preferably 0.1 mol % or less, based on the number of moles of all structural units constituting the vinyl ester polymer.

[0036] The polymerization degree of PVA is not particularly limited, but is preferably 1,000 or more. The polymerization degree of PVA is preferably 8,000 or less. From the viewpoint of improving the optical performance (light transmittance, polarizing property, etc.) and moist heat resistance of the obtained optical film, the polymerization degree of PVA is more preferably 1,500 or more, and more preferably 2,000 or more. On the other hand, from the viewpoint of improving the productivity of PVA, the polymerization degree of PVA is more preferably 5,000 or less, and even more preferably 4,000 or less.

[0037] Here, the degree of polymerization means the average degree of polymerization measured in accordance with the description of JIS K 6726-1994. That is, in the present invention, the degree of polymerization (Po) is calculated from the intrinsic viscosity [η] (dl / g) measured in water at 30°C after resaponifying the residual acetate groups of PVA and purifying it, according to the following formula: Degree of polymerization Po = ([η]×10 4 / 8.29) (1 / 0.62)

[0038] In the present invention, the lower limit of the saponification degree of PVA is preferably 98.7 mol%, more preferably 99.0 mol%, even more preferably 99.5 mol%, particularly preferably 99.8 mol%, and preferably 99.9 mol%. By having the saponification degree be equal to or higher than the above lower limit, an optical film having excellent optical performance and moist heat resistance can be obtained. On the other hand, there is no particular limit to the upper limit of the saponification degree, but from the viewpoint of productivity of PVA, the upper limit of the saponification degree is preferably 99.99 mol%.

[0039] Here, the saponification degree of PVA refers to the ratio (mol%) of the number of moles of vinyl alcohol units to the total number of moles of structural units (typically vinyl ester monomer units) that can be converted to vinyl alcohol units by saponification and vinyl alcohol units. The saponification degree of PVA can be measured according to the description of JIS K 6726-1994.

[0040] The PVA film of the present invention may contain one type of PVA alone, or may contain two or more types of PVA differing from each other in the degree of polymerization, degree of saponification, degree of modification, and the like.

[0041] The upper limit of the PVA content in the PVA film is not particularly limited, while the lower limit of the PVA content is preferably 50% by mass, more preferably 80% by mass, and even more preferably 85% by mass.

[0042] (Plasticizer) The PVA film of the present invention preferably contains a plasticizer. By containing a plasticizer in the PVA film, the stretchability of the PVA film can be improved in the stretching step when manufacturing an optical film such as a polarizing film. The plasticizer is preferably a polyhydric alcohol. Examples of the polyhydric alcohol include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane. Among these, glycerin is preferred from the viewpoint of the effect of improving the stretchability. The plasticizer can be used alone or in combination of two or more.

[0043] By adjusting the content of the plasticizer in the PVA film, the amount of lamellar crystals or the size of the lamellar crystals can be adjusted. Although it depends on the primary structure of the molecular chain of PVA, in general, crystal growth is more likely to proceed by heat treatment in a PVA film containing a small amount of plasticizer than in a PVA film that does not contain plasticizer. This is presumed to be because a small amount of plasticizer makes the PVA molecules in the PVA film more mobile and makes it easier to form a more energetically stable crystal structure. As the crystal growth of the PVA film progresses, the size of the lamellar crystals in the PVA film increases, and the crystal long period Da tends to increase. On the other hand, if the PVA film contains an excessive amount of plasticizer, the crystal growth is more likely to be inhibited. This is presumed to be because the amount of plasticizer that interacts with the hydroxyl groups of the PVA molecules increases, weakening the interaction between the PVA molecules. In addition, if the PVA film contains a plasticizer, the amorphous part is more likely to absorb water, and the increase rate of the crystal long period tends to increase.

[0044] From the viewpoint of adjusting the size of the lamellar crystals in the PVA film to an appropriate range and adjusting the crystal long period Da and the increase rate of the crystal long period, the content of the plasticizer is preferably 3 parts by mass or more relative to 100 parts by mass of PVA. In addition, the content of the plasticizer is preferably 20 parts by mass or less relative to 100 parts by mass of PVA. In both cases where the content of the plasticizer is less than 2 parts by mass relative to 100 parts by mass of PVA and more than 20 parts by mass, the size of the lamellar crystals in the PVA film tends to be too small. As a result, the crystal long period Da becomes small, and there is a risk that the increase rate of the crystal long period of the PVA film will be outside the specified range. The content of the plasticizer is more preferably 5 parts by mass or more, and more preferably 8 parts by mass or less, relative to 100 parts by mass of PVA. In addition, the content of the plasticizer is more preferably 17 parts by mass or more, and more preferably 15 parts by mass or less.

[0045] (Surfactant) The PVA film of the present invention preferably contains a surfactant. By producing a PVA film using a film-forming solution containing a surfactant, the film-forming properties of the PVA film are improved. As a result, the occurrence of thickness unevenness in the PVA film is suppressed, and the PVA film is easily peeled off from a metal roll or belt used in film formation. When a PVA film is produced from a film-forming solution containing a surfactant, the resulting PVA film contains the surfactant.

[0046] The type of surfactant is not particularly limited, but from the viewpoint of the peelability of the PVA film from the metal roll or belt, anionic surfactants and nonionic surfactants are preferred.

[0047] Examples of anionic surfactants include carboxylic acid types such as potassium laurate; sulfate types such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid types such as dodecylbenzenesulfonate.

[0048] Examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether.

[0049] The surfactants can be used alone or in combination of two or more.

[0050] When the PVA film contains a surfactant, the lower limit of the surfactant content in the PVA film is preferably 0.01 parts by mass, more preferably 0.02 parts by mass, and even more preferably 0.05 parts by mass, relative to 100 parts by mass of PVA. By making the surfactant content equal to or greater than the lower limit, the film-forming property and peelability of the PVA film are further improved. On the other hand, the upper limit of the surfactant content in the PVA film is preferably 0.5 parts by mass, more preferably 0.3 parts by mass, and even more preferably 0.2 parts by mass, relative to 100 parts by mass of PVA. By making the surfactant content equal to or less than the upper limit, it is possible to prevent the surfactant from bleeding out onto the surface of the PVA film, causing blocking and reducing the handleability.

[0051] (Other additives, etc.) The PVA film of the present invention may further contain additives, such as fillers, processing stabilizers such as copper compounds, weather resistance stabilizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, antifoaming agents, deodorants, extenders, peeling agents, release agents, reinforcing agents, crosslinking agents, mildew inhibitors, preservatives, and crystallization rate retarders, as necessary.

[0052] In the PVA film of the present invention, the total proportion of PVA, plasticizer, and surfactant is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and in some cases even more preferably 99% by mass or more. Since the PVA film of the present invention is substantially composed of PVA, plasticizer, and surfactant, when a polarizing film is produced using the PVA film of the present invention, a polarizing film with excellent polarization performance can be obtained.

[0053] (shape, physical properties, etc.) The PVA film of the present invention is used as a material for optical films, that is, a raw film for producing optical films, although the PVA film of the present invention is not limited to being in a roll form.

[0054] The average thickness of the PVA film of the present invention is not particularly limited. The lower limit of the average thickness of the PVA film is preferably 1 μm, more preferably 5 μm, even more preferably 10 μm, and particularly preferably 15 μm. When the average thickness is equal to or greater than the above lower limit, the breakage of the PVA film can be suppressed during the stretching process when manufacturing an optical film such as a polarizing film. On the other hand, the upper limit of the average thickness of the PVA film is preferably 60 μm, more preferably 50 μm, even more preferably 45 μm, and even more preferably 35 μm. When the average thickness is equal to or less than the above upper limit, the effect of the present invention can be fully exhibited. The term "average thickness" refers to the average value of thicknesses measured at any five points (hereinafter, the same applies to the average thickness).

[0055] The PVA film of the present invention may be a monolayer film consisting of one PVA layer, or may be a multilayer film containing one PVA layer. However, when the PVA film of the present invention is used as a raw film for manufacturing a polarizing film, it is preferably a monolayer film. When the PVA film of the present invention is included as a PVA layer of a multilayer film, the lower limit of the average thickness of the PVA layer is preferably 1 μm, more preferably 5 μm, even more preferably 10 μm, and particularly preferably 15 μm. When the average thickness is equal to or greater than the above lower limit, breakage of the PVA film can be suppressed in the stretching step when manufacturing an optical film such as a polarizing film. In addition, the upper limit of the average thickness of the PVA layer is preferably 60 μm, more preferably 50 μm, even more preferably 45 μm, and even more preferably 35 μm. When the average thickness is equal to or less than the above upper limit, the effect of the present invention can be fully exhibited.

[0056] The multilayer film refers to a film having two or more layers. The number of layers of the multilayer film may be 5 or less, or 3 or less. The multilayer film may be a laminated film having a laminated structure of a base resin layer and a PVA layer. The average thickness of the base resin layer is preferably, for example, 20 μm or more. The average thickness of the base resin layer is preferably, for example, 500 μm or less. The base resin layer in the multilayer film is preferably one that can be uniaxially stretched together with the PVA layer. As the resin constituting the base resin layer, polyester, polyolefin, etc. can be used. Among them, amorphous polyester is preferable, and amorphous polyester obtained by copolymerizing polyethylene terephthalate with a copolymerization component such as isophthalic acid or 1,4-cyclohexanedimethanol is preferably used. An adhesive layer may be provided between the base resin layer and the PVA layer.

[0057] The width of the PVA film of the present invention is not particularly limited and can be determined depending on the application. For example, the lower limit of the width of the PVA film is preferably 3 m. The lower limit of the width is 3 m, which is suitable for use in liquid crystal televisions and liquid crystal monitors, which have become larger in size in recent years. In particular, the PVA film of the present invention can suppress the occurrence of swelling wrinkles in the PVA film during the swelling process when producing an optical film such as a polarizing film, and can therefore be suitably used when producing an optical film with a width of 3 m or more, which is difficult to produce. On the other hand, the upper limit of the width of the PVA film is preferably 7 m. By setting the upper limit of the width to 7 m, when producing an optical film such as a polarizing film using a practical device, a stretching process (uniaxial stretching process) can be efficiently performed.

[0058] The swelling degree of the PVA film of the present invention is preferably 140% or more from the viewpoint of the productivity and optical performance of the obtained optical film. The swelling degree of the PVA film of the present invention is preferably 400% or less. The lower limit of the swelling degree is more preferably 170%, further preferably 180%, and particularly preferably 190%. The upper limit of the swelling degree is more preferably 220%, and further preferably 210%. The swelling degree of the PVA film can be adjusted to a smaller value, for example, by increasing the temperature of the heat treatment of the PVA film.

[0059] Here, the "degree of swelling of the PVA film" refers to a value calculated by the following formula. Swelling degree (%)=100×N / M In the formula, N represents the mass (g) of a sample taken from a PVA film after immersing it in distilled water at 30°C for 30 minutes and removing the water from the surface, and M represents the mass (g) of the sample after drying it in a dryer at 105°C for 16 hours.

[0060] The PVA film of the present invention is usually a film that is not substantially stretched (unstretched film, non-stretched film). Also, the in-plane retardation of the PVA film is preferably 100 nm or less, more preferably 50 nm or less. Usually, an optical film can be obtained by subjecting the PVA film of the present invention to a stretching treatment (uniaxial stretching treatment or biaxial stretching treatment).

[0061] According to the PVA film of the present invention, in the swelling step when manufacturing an optical film such as a polarizing film, the occurrence of swelling wrinkles in the PVA film can be suppressed, and an optical film such as a thin polarizing film can be manufactured with good productivity. Examples of the optical film that can be manufactured using the PVA film of the present invention include a polarizing film, a retardation film, a viewing angle improvement film, a brightness improvement film, etc., and a polarizing film is preferred.

[0062] <Manufacturing method of PVA film> In the present invention, the film-forming method of the PVA film uses a film-forming stock solution obtained by adding a solvent, an additive, etc. to PVA and homogenizing it, and is a casting film-forming method, a wet film-forming method (discharge into a poor solvent), a dry-wet film-forming method, a gel film-forming method (a method of once cooling and gelling the film-forming stock solution and then extracting and removing the solvent to obtain a PVA-based polymer film), or a method of forming a film by a combination of these, or a melt extrusion film-forming method or an inflation molding method of obtaining the above film-forming stock solution using an extruder and extruding it from a T-die or the like. The film can be formed by any method. Among these, the casting film-forming method and the melt extrusion film-forming method are preferred because a homogeneous film can be obtained with good productivity. Hereinafter, the casting film-forming method or the melt extrusion film-forming method of the PVA film will be described.

[0063] When the PVA film is produced by the casting film production method or the melt extrusion film production method, the film-forming solution is cast in the form of a film onto a support such as a metal roll or a metal belt, and is solidified into a film by heating to remove the solvent. The solidified film is peeled off from the support, dried by a drying roll or a drying oven as necessary, and further heat-treated as necessary, and wound up to obtain a long roll of PVA film.

[0064] The membrane-forming solution (hereinafter sometimes referred to as "PVA film") dripped onto the support undergoes crystallization while being heated and dried on the support and in the subsequent drying process. In particular, when the membrane-forming solution is heated in a state of high volatile content (moisture content), the mobility of the PVA molecular chains in the membrane-forming solution (PVA film) increases, and crystallization proceeds. As a result, the amount of lamellar crystals in the PVA film increases, and the crystal long period Da tends to decrease. Here, if the drying speed is too fast, the crystallization of the PVA film does not proceed sufficiently, the amount of lamellar crystals decreases, and the crystal long period Da tends to increase. On the other hand, if the drying speed is too slow, the crystal growth of the PVA film proceeds, the size of the lamellar crystals increases, and the crystal long period Da tends to increase. In addition, if too much heat is applied during drying, the size of the lamellar crystals in the PVA film tends to increase, and the crystal long period Da tends to become too large or the increase rate of the crystal long period tends to become too small.

[0065] The volatile content of the film-forming solution (the proportion of volatile components such as solvents that are removed by volatilization or evaporation during film formation) is preferably 50% by mass or more, more preferably 55% by mass or more. The volatile content of the film-forming solution is preferably 90% by mass or less, more preferably 80% by mass or less. If the volatile content is less than 50% by mass, the viscosity of the film-forming solution increases, which may make it difficult to form a PVA film. On the other hand, if the volatile content concentration exceeds 90% by mass, the viscosity decreases, which may impair the uniformity of the thickness of the PVA film.

[0066] Here, the "volatile content of the membrane-forming solution" in the present invention refers to the volatile content calculated by the following formula. Volatile content of film-forming solution (mass%) = {(Wa-Wb) / Wa} x 100 (In the formula, Wa represents the mass (g) of the film-forming solution, and Wb represents the mass (g) of the film-forming solution Wa (g) after drying it in an electric dryer at 105°C for 16 hours.)

[0067] There is no particular limitation on the method for preparing the film-forming solution. Examples of the method include dissolving PVA and additives such as a plasticizer and a surfactant in a dissolution tank, and melt-kneading PVA in a water-containing state together with a plasticizer, a surfactant, etc., using a single-screw or twin-screw extruder.

[0068] When a PVA film is produced by a casting method or a melt extrusion method, the above-mentioned film-forming solution is cast in the form of a film onto a support such as a metal roll or a metal belt from a film-like discharge device, and is heated to remove the solvent, thereby solidifying and forming a film.

[0069] The increase rate of the crystal long period of the PVA film of the present invention before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8) is within a specific range. This increase rate is presumably affected by the degree of entanglement of the PVA molecular chains in the amorphous parts present between the lamellar crystals in the PVA film. Therefore, the increase rate of the crystal long period of the PVA film can be controlled by adjusting the shear rate at the outlet of the film-like extrusion device, where the film-forming solution is subjected to a strong shear force. From this perspective, the shear rate at the outlet of the film-like extrusion device is set to 75 s -1 It is preferable that the temperature is 100s or more. -1 More preferably, 125s or more. -1 It is more preferable that the shear rate at the outlet of the film-like discharge device is 1000 s -1 It is preferable that the temperature is 900s -1 It is more preferable that it is less than 800s -1If the shear rate is outside the above range, the amorphous part of the PVA film tends to take up too much water contained in the swelling treatment bath during the swelling step in producing an optical film such as a polarizing film.

[0070] In the present invention, the shear rate at the outlet of the film-like extrusion device refers to the shear rate at the wall surface of the film-forming liquid flow path at the die lip in the case of a general T-die or I-die, and can be calculated by the following formula. γ=6Q / Wh 2 where γ is the shear rate at the wall (s -1 ), W is the width of the die lip (cm), h is the opening of the die lip (cm), and Q is the extrusion speed of the film-forming solution from the die lip (cm 3 / s).

[0071] The surface temperature of the support on which the film-forming solution flows is preferably 50°C or higher. The surface temperature of the support on which the film-forming solution flows is preferably 110°C or lower. If the surface temperature is lower than 50°C, the time required for drying the film-forming solution is longer, and the productivity tends to decrease. On the other hand, if the surface temperature exceeds 110°C, the surface of the PVA film tends to be easily abnormal due to foaming or the like. In addition, the crystallization of the PVA film does not proceed sufficiently due to the rapid drying of the film-forming solution, and the amount of lamellar crystals tends to decrease, and the crystal long period Da tends to increase. From the viewpoint of easily adjusting the rate of increase in the crystal long period of the PVA film, the surface temperature of the support is preferably 60°C or higher, more preferably 65°C or higher. In addition, the surface temperature of the support is preferably 100°C or lower, more preferably 95°C or lower.

[0072] The drying speed may be adjusted by uniformly blowing hot air at a speed of 1 to 10 m / sec onto the entire area of ​​the non-contact side of the PVA film while heating the PVA film on the support. The temperature of the hot air blown onto the non-contact side is preferably 50° C. or higher, more preferably 70° C. or higher, from the viewpoints of drying efficiency and drying uniformity. The temperature of the hot air blown onto the non-contact side is preferably 150° C. or lower, more preferably 120° C. or lower, from the viewpoints of drying efficiency and drying uniformity.

[0073] The PVA film is dried on the support preferably to a volatile content of 5 to 50% by mass, and then peeled off, and further dried as necessary. There is no particular limitation on the drying method, and examples include a method of contacting the film with a drying oven or a drying roll. When drying is performed with a plurality of drying rolls, it is preferable to alternately contact one side and the other side of the film with the drying rolls in order to make both sides uniform. The number of drying rolls is preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. In addition, the number of drying rolls is even more preferably 30 or less. The temperature of the drying oven or the average temperature of the drying rolls (average surface temperature of the drying rolls) is preferably 110° C. or less, more preferably 100° C. or less, more preferably 90° C. or less, and even more preferably 85° C. or less. If the temperature of the drying oven or the average temperature of the drying rolls is too high, the crystal growth of the PVA film proceeds, and the size of the lamellar crystals in the PVA film tends to increase. As a result, the crystal long period Da increases, and there is a risk that the increase rate of the crystal long period becomes too small. On the other hand, the temperature of the drying oven or the average temperature of the drying roll is preferably 40° C. or higher, more preferably 45° C. or higher, and even more preferably 50° C. or higher. If the temperature of the drying oven or the average temperature of the drying roll is too low, the crystal growth of the PVA film becomes insufficient, and the size of the lamellar crystals in the PVA film tends to become small. As a result, there is a risk that the crystal long period Da becomes too small or the increase rate of the crystal long period becomes too large.

[0074] The dried PVA film can be further heat-treated as necessary. By carrying out the heat treatment, the strength, swelling degree, birefringence, etc. of the PVA film can be adjusted. The surface temperature of the heat treatment roll for carrying out the heat treatment is preferably 60°C or higher. The surface temperature of the heat treatment roll is preferably 135°C or lower, more preferably 130°C or lower. If the surface temperature of the heat treatment roll is too high, the amount of heat applied is too large, and the size of the lamellar crystals in the PVA film tends to become large, and the crystal long period Da tends to become too large or the increase rate of the crystal long period tends to become too small.

[0075] The PVA film produced in this manner may be further subjected to moisture conditioning treatment, cutting of both ends (edges) of the film, etc., as necessary, wound into a roll on a cylindrical core, and then packaged in moisture-proof packaging to complete the product.

[0076] Although the volatile content of the PVA film finally obtained by the above-mentioned series of treatments is not necessarily limited, the volatile content of the PVA film is preferably 1% by mass or more, more preferably 2% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less.

[0077] When the PVA film of the present invention is a multilayer film, the multilayer film can be produced, for example, by applying a film-forming solution onto a base resin film (base resin layer). At this time, in order to improve the adhesion between the PVA layer and the base resin layer, the surface of the base resin film may be modified or an adhesive may be applied to the surface of the base resin film.

[0078] <Method of manufacturing optical film> The method for producing an optical film of the present invention includes a step of uniaxially stretching the above-mentioned PVA film. Hereinafter, a method for producing a polarizing film will be specifically described as an example of the method for producing an optical film.

[0079] Examples of the method for producing a polarizing film include a dyeing step for dyeing a PVA film, a stretching step for uniaxial stretching, and, if necessary, a swelling step for swelling, a crosslinking step for crosslinking, a fixing step for fixing, a washing step for washing, a drying step for drying, and a heat treatment step for heat treatment. In this case, the order of each step is not particularly limited, and for example, the steps can be performed in the order of a swelling step, a dyeing step, a crosslinking step, a stretching step, and a fixing step. In addition, one or more steps can be performed simultaneously, and each step can be performed twice or more times. In particular, the PVA film of the present invention can suppress the occurrence of swelling wrinkles in the swelling step, and is therefore useful as a film used in a method for producing a polarizing film having a swelling step.

[0080] The swelling step can be carried out by immersing the PVA film in a swelling treatment bath containing water and the like. The temperature of the swelling treatment bath is preferably 20°C or higher, more preferably 22°C or higher, and even more preferably 25°C or higher. The temperature of the swelling treatment bath is preferably 55°C or lower, more preferably 50°C or lower, and even more preferably 45°C or lower. The time of immersion in the swelling treatment bath is preferably, for example, 0.1 minutes or more, and more preferably 0.5 minutes or more. The time of immersion in the swelling treatment bath is preferably, for example, 5 minutes or less, and more preferably 3 minutes or less. The water used in the swelling treatment bath is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and an aqueous medium.

[0081] The dyeing process can be carried out by contacting the PVA film with a solution (dyeing bath) containing a dichroic dye. An iodine-based dye is generally used as the dichroic dye. The timing of dyeing may be any stage before, during, or after uniaxial stretching. The dyeing bath is preferably a solution containing iodine-potassium iodide, and this solution is preferably an aqueous solution. The iodine concentration in the dyeing bath is preferably 0.01% by mass or more. The iodine concentration is preferably 0.5% by mass or less. The potassium iodide concentration is preferably 0.01% by mass or more. The potassium iodide concentration is preferably 10% by mass or less. The temperature of the dyeing bath is preferably 20° C. or more, more preferably 25° C. or more. The temperature of the dyeing bath is preferably 50° C. or less, more preferably 40° C. or less. The dyeing time is preferably 0.2 minutes or more. The dyeing time is preferably 5 minutes or less.

[0082] By carrying out a crosslinking step in which the PVA in the PVA film is crosslinked, it is possible to effectively prevent the PVA from dissolving into water during wet stretching at high temperatures. From this viewpoint, it is preferable to carry out the crosslinking step after the dyeing step and before the stretching step. The crosslinking step can be carried out by immersing the PVA film in an aqueous solution (crosslinking treatment bath) containing a crosslinking agent. As the crosslinking agent, one or more boron compounds such as boric acid and borax or other borates can be used. The concentration of the crosslinking agent in the crosslinking treatment bath is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass or more. In addition, the concentration of the crosslinking agent is preferably 15% by mass or less, more preferably 7% by mass or less, and even more preferably 6% by mass or less. When the concentration of the crosslinking agent is within the above range, the stretchability of the PV film can be sufficiently maintained. The crosslinking treatment bath may contain potassium iodide or the like. The temperature of the crosslinking treatment bath is preferably 20° C. or more, and more preferably 25° C. or more. The temperature of the crosslinking treatment bath is preferably not higher than 60° C., and more preferably not higher than 55° C. By keeping the temperature within the above range, the PVA film can be efficiently crosslinked.

[0083] The stretching step of uniaxially stretching the PVA film may be performed by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, it may be performed in an aqueous solution (stretching treatment bath) containing boric acid, or in the dyeing treatment bath described above or in the fixing treatment bath described below. In the case of the dry stretching method, the stretching may be performed at room temperature (25°C), or may be performed while heating, or may be performed in air using the PVA film after absorbing water. Among these, the wet stretching method is preferred because it can be stretched with high uniformity in the width direction, and uniaxial stretching in a stretching treatment bath is more preferred. The concentration of boric acid in the stretching treatment bath is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 1.5% by mass or more. In addition, the concentration of boric acid is preferably 6.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 4.0% by mass or less. The stretching bath may contain potassium iodide, and the concentration of potassium iodide is preferably 0.01% by mass or more. The concentration of potassium iodide is preferably 10% by mass or less. The stretching temperature in the uniaxial stretching is preferably 30° C. or more, more preferably 40° C. or more, and even more preferably 50° C. or more. The stretching temperature in the uniaxial stretching is preferably 90° C. or less, more preferably 80° C. or less, and even more preferably 75° C. or less.

[0084] The stretching ratio in the uniaxial stretching (total stretching ratio from the non-stretched PVA film) is preferably 5 times or more, more preferably 5.5 times or more, from the viewpoint of the polarizing performance of the resulting polarizing film. There is no particular upper limit to the stretching ratio, but the stretching ratio is preferably 8 times or less.

[0085] When a long PVA film is uniaxially stretched, the direction of uniaxial stretching is not particularly limited, and uniaxial stretching in the long direction or uniaxial stretching in the transverse direction can be adopted. Since a polarizing film having excellent polarization performance can be obtained, uniaxial stretching in the long direction is preferred. Uniaxial stretching in the long direction can be performed by using a stretching device equipped with multiple rolls parallel to each other and changing the peripheral speed between the rolls. On the other hand, uniaxial stretching in the transverse direction can be performed using a tenter type stretching machine.

[0086] In the production of a polarizing film, a fixing process can be performed after the stretching process in order to strengthen the adsorption of the dichroic dye (such as an iodine-based dye) to the PVA film. As the fixing bath used for the fixing process, an aqueous solution containing one or more boron compounds such as boric acid and borax can be used. In addition, an iodine compound or a metal compound may be added to the fixing bath as necessary. The concentration of the boron compound in the fixing bath is preferably 2% by mass or more, more preferably 3% by mass or more. In addition, the concentration of the boron compound is preferably 15% by mass or less, more preferably 10% by mass or less. By setting the concentration of the boron compound within the above range, the adsorption of the dichroic dye can be strengthened. The temperature of the fixing bath is preferably 15° C. or more, more preferably 25° C. or more. In addition, the temperature of the fixing bath is preferably 60° C. or less, more preferably 40° C. or less.

[0087] The cleaning step is generally performed by immersing the film in distilled water, pure water, an aqueous solution, or the like. In this case, it is preferable to use an aqueous solution (cleaning bath) containing an iodide such as potassium iodide as an auxiliary agent from the viewpoint of improving the polarization performance. The concentration of the iodide is preferably 0.5% by mass or more. The concentration of the iodide is preferably 10% by mass or less. The temperature of the cleaning bath is preferably 5° C. or more, more preferably 10° C. or more, and even more preferably 15° C. or more. The temperature of the cleaning bath is preferably 50° C. or less, more preferably 45° C. or less, and even more preferably 40° C. or less. By setting the temperature of the cleaning bath within the above range, the polarization performance can be further improved.

[0088] Although the conditions for the drying step are not particularly limited, the drying temperature for the PVA film is preferably 30° C. or higher, and more preferably 50° C. or higher. The drying temperature for the PVA film is preferably 150° C. or lower, and more preferably 130° C. or lower. Drying at a temperature within the above range makes it easier to obtain a polarizing film with excellent dimensional stability.

[0089] In addition, optical films other than polarizing films, such as retardation films, can also be produced by a method including a step of uniaxially stretching the PVA film of the present invention. As for the specific production method, a conventionally known method can be adopted except that the PVA film of the present invention is used.

[0090] The polarizing film obtained as described above is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on either or both sides of the polarizing film. Examples of the protective film include cellulose triacetate (TAC) film, cycloolefin polymer (COP) film, cellulose acetate butyrate (CAB) film, acrylic film, and polyester film. Examples of adhesives used for lamination include PVA adhesives, urethane adhesives, and acrylate ultraviolet-curing adhesives. That is, a polarizing plate has a polarizing film and a protective film laminated on either or both sides of the polarizing film directly or via an adhesive layer.

[0091] The polarizing plate can be used as a part of an LCD by, for example, coating it with an acrylic adhesive and then bonding it to a glass substrate. Note that the polarizing plate may further be bonded with a retardation film, a viewing angle improving film, a brightness improving film, etc. EXAMPLES

[0092] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. The evaluation items and methods adopted in the following examples and comparative examples are as follows.

[0093] (1) Long crystallographic periods Ds and Da of PVA film Using the above method, small-angle X-ray measurement was performed on the PVA films obtained in the following Examples and Comparative Examples before and after immersion in a water / methanol mixed solvent (volume ratio: 2 / 8). Specifically, first, the PVA film was cut into multiple pieces of 2 cm x 1 cm size, regardless of the width direction (TD direction) or machine flow direction (MD direction). The cut PVA films were stored for 24 hours under conditions of a temperature of 20°C and a humidity of 65%, and then 10 sheets were stacked in a measurement cell to obtain a measurement sample. Small-angle X-ray scattering measurement was performed on this measurement sample in air (temperature 20°C, humidity 65%) to obtain a scattering curve. The scattering vector q (nm -1) was used to calculate the crystal long period Da according to the following formula. Crystal long period Da(nm) = 2π / q

[0094] In addition, the PVA films obtained in the following Examples and Comparative Examples were cut into multiple pieces of 2 cm x 1 cm size, regardless of the width direction (TD) or machine direction (MD). The cut PVA films were immersed in a water / methanol mixed solvent (volume ratio: 2 / 8) for 24 hours, and then 10 pieces were stacked in a measurement cell filled with the mixed solvent to obtain a measurement sample. Small angle X-ray scattering measurement was performed on this measurement sample, and a scattering curve was obtained. The scattering vector q (nm -1 ) was used to calculate the crystal long period Ds according to the following formula. Crystal long period Ds (nm) = 2π / q

[0095] (2) Swelling degree of PVA film The swelling degree of the PVA films obtained in the following Examples and Comparative Examples was determined by the above-mentioned method.

[0096] (3) Evaluation of swelling and wrinkles on PVA film The swelling wrinkles were evaluated using a film roll with a width of 65 cm obtained by slitting the PVA film obtained in the following Examples and Comparative Examples. First, the PVA film was unwound from the film roll and then stretched 2.0 times in the MD direction in pure water (swelling treatment bath) at 33°C. Then, it was stretched to a total stretch ratio of 2.4 times in an aqueous solution (dyeing treatment bath) at 32°C containing 0.03 mass% iodine and 0.7 mass% potassium iodide. At this time, the occurrence of swelling wrinkles in the PVA film at the exit of the swelling treatment bath was observed and evaluated according to the following criteria. A: Almost no swelling wrinkles were observed. B: Three to four swelling wrinkles appear, but they disappear in the dyeing bath. C: Severe swelling wrinkles occurred, and swelling wrinkles were observed even in the dyeing treatment bath.

[0097] (4) Optical performance of polarizing film A polarizing film was produced using the PVA film obtained in the following examples and comparative examples. First, the PVA film was stretched 2.0 times in the MD direction in pure water (swelling treatment bath) at 25 ° C., and then stretched to a total stretch ratio of 2.4 times in an aqueous solution (dyeing treatment bath) at 32 ° C. containing 0.03 mass% iodine and 0.7 mass% potassium iodide. Next, it was stretched to a total stretch ratio of 3.0 times in an aqueous solution (crosslinking treatment bath) at 32 ° C. containing 2.6 mass% boric acid, and further stretched to a total stretch ratio of 6.0 times in an aqueous solution (stretching treatment bath) at 58 ° C. containing 2.8 mass% boric acid and 5.0 mass% potassium iodide. Next, it was immersed in an aqueous solution (cleaning treatment bath) at 22 ° C. containing 1.5 mass% boric acid and 2.5 mass% potassium iodide for 5 seconds, and dried in a drying oven at 80 ° C. for 4 minutes.

[0098] A rectangular measurement sample measuring 4 cm in the machine direction (MD) and 1.5 cm in the width direction (TD) of the obtained polarizing film was taken from the center of the width direction (TD) of the polarizing film. The single transmittance and polarization degree of this measurement sample were measured using an integrating sphere spectrophotometer (JASCO Corporation's "V7100") in accordance with JIS Z8722 (measurement method for object color) after luminosity correction in the visible light region with a C light source and a 2° field of view.

[0099] (5) Moisture and heat resistance of polarizing film The polarizing films obtained in the following Examples and Comparative Examples were fixed to a metal frame, and the single transmittance (T0) was measured using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) in accordance with JIS Z8722 (measurement method for object color) after luminosity correction in the visible light region with a C light source and a 2° field of view. Furthermore, the polarizing films fixed to the metal frame were subjected to a wet heat treatment for 12 hours in an atmosphere of 60°C and 90% RH, and then the transmittance (T0) was measured using the spectrophotometer under the same conditions. 12 The decrease in transmittance after the moist heat treatment (T0-T 12 :%) was used as an index of moist heat resistance.

[0100] <Example 1> A film-forming stock solution with a volatile content of 73% by mass was prepared by saponifying polyvinyl acetate (100 parts by mass of PVA (saponification degree 99.9 mol%, polymerization degree 2400), 9 parts by mass of glycerin as a plasticizer, 0.1 parts by mass of lauric acid diethanolamide as a surfactant, and water. The filtered film-forming stock solution was passed through a T-die at a shear rate of 207 s -1 The film was discharged onto a support (surface temperature 90°C) at 100°C, and dried by blowing hot air at 85°C at a speed of 5m / sec onto the entire surface of the support that was not in contact with the support. The film was then peeled off from the support, and further dried between the first drying roll and the final drying roll (19th drying roll) immediately before the heat treatment roll so that one side and the other side of the PVA film alternately contacted each drying roll, and then peeled off from the final drying roll. At this time, the average surface temperature of each drying roll from the first drying roll to the final drying roll was set to 55°C. Finally, the film was heat-treated with a heat treatment roll with a surface temperature of 110°C, and then wound into a roll to obtain a PVA film (thickness 45μm, width 3.3m).

[0101] The small angle X-ray scattering measurement of the obtained PVA film showed that the crystal long period Da was 12.1 nm, the crystal long period Ds was 14.5 nm, and the increase rate of the crystal long period was 0.20. The swelling degree of the PVA film was also measured and found to be 195%.

[0102] The resulting PVA film was used to evaluate swelling wrinkles, and almost no swelling wrinkles were observed in the swelling treatment bath, earning it an A rating. A polarizing film was then produced and its optical performance was measured, with a transmittance of 44.1% and a polarization degree of 99.831%. The polarizing film's resistance to moist heat was also evaluated, with a transmittance of 49.9% after 12 hours and a transmittance change of 5.8%.

[0103] <Example 2, Example 3 and Comparative Example 1> A PVA film was obtained in the same manner as in Example 1, except that the amount of plasticizer and the production conditions were changed as shown in Table 1.

[0104] <Comparative Example 2> A PVA film was obtained in the same manner as in Example 1, except that a PVA having a degree of saponification of 99.2 mol % and a degree of polymerization of 2400 was used and the amount of plasticizer and the production conditions were changed as shown in Table 1.

[0105] The evaluation results of the obtained PVA film are shown in Table 1.

[0106] [Table 1]

[0107] As is clear from Table 1, the PVA film of the present invention can suppress the occurrence of swelling wrinkles in the swelling step when manufacturing an optical film such as a polarizing film, even when the PVA film has a relatively thin thickness of 45 μm. As a result, the PVA film can be suppressed from breaking in the stretching step when manufacturing an optical film such as a polarizing film, and a thin optical film such as a polarizing film can be manufactured with good productivity. In particular, the PVA film of Example 1, which has a crystal long period Ds of 16 nm or less, provides a polarizing film with particularly excellent moist heat resistance. [Explanation of symbols]

[0108] 1 Peak top of scattering curve 2. Auxiliary line for setting the scattering vector q at the peak top of the scattering curve 3 Scattering vector q at the peak top of the scattering curve

Claims

1. A polyvinyl alcohol film, in which the crystalline long period Ds determined by small-angle X-ray scattering measurement performed in a water / methanol mixed solvent (volume ratio: 2 / 8) and the crystalline long period Da determined by small-angle X-ray scattering measurement performed before immersion in the mixed solvent satisfy the following formula: 0.15≦(Ds-Da) / Da<0.3

2. 2. The polyvinyl alcohol film according to claim 1, wherein the crystal long period Ds is 12.0 to 16.0 nm.

3. The polyvinyl alcohol film according to claim 1 or 2, wherein the average thickness of the film is 15 to 60 μm.

4. The polyvinyl alcohol film according to claim 1 , which is a raw film for producing an optical film.

5. A method for producing an optical film, comprising uniaxially stretching the polyvinyl alcohol film according to claim 1 .

6. The method for producing an optical film according to claim 5 , further comprising a swelling step of swelling the polyvinyl alcohol film.

Citation Information

Patent Citations

  • New polyvinyl alcohol and production of polyvinyl alcohol by acid saponification

    JP1990255806A

  • Producing method for polyvinyl alcohol-base polymer film

    JP2001315146A

  • Polyvinyl alcohol type film for polarizing film

    JP2002062429A

  • Polyvinyl alcohol film and method for producing the same

    JP2006188655A

  • Microregion dispersing type polyvinyl alcohol film, its manufacturing method, manufacturing method of polarizer, polarizer, polarizing plate, optical film and image display device

    JP2006224430A